Antioxidant Activity of Leave's Extract and Isolate Ketepeng Kebo Cassia alata Linn (Leguminoceae) - Masruri Masruri; Rurini R Rurini R; Dasrul Dasrul; Aulann'iam Aulann'iam (Jurnal Kedokteran Syiah Kuala, 2007)
Abstract.    Phytochemistry and biological    activity investigation  of medical  plants was an important step in exploring of their potency. The objectives  of this research were to determine the antioxidant activity of the extract and purified isolate of C. alata  leave and also,  to  elucidate of  the molecular structure of  the  responsible molecule. The methods used were extraction,  isolation and purification by means of chromatography, DPPH radical scavenging and spectroscopy. Result of the research provided antioxidant activity was (ED5o)   28.50±1.86 µg/mL for  the extract and 9.99±0.28  µM  for  the  purified  isolate.  Elucidation toward  the  purified  isolate indicated   kaemferol   structure   as   the   most   active   antioxidant   compound. (JKS 2007; 3: 125 - 130)